Do key performance indicators matter on public procurement rules 2008? an empirical study on Local Government Engineering Department, Bangladesh - Rahman, Mahfuzar; Islam, Zohurul; Das, Amrita Kumar (PrAcademics Press, 2016)
This article was published in the Journal of Public Procurement [ © 2015 by PrAcademics Press ] and the Article's website is at: http://pracademics.com/attachments/article/1208/Artile%205_Rahman-Das.pdf